Impact of protected areas on poverty, extreme poverty, and inequality in Nepal. Issue 6 (4th July 2018) - den Braber, Bowy; Evans, Karl L.; Oldekop, Johan A.
Abstract: Protected areas (PAs) are key for biodiversity conservation, but there are concerns that they can exacerbate poverty or unequal access to potential benefits, such as those arising from tourism. We assess how Nepalese PAs influence poverty, extreme poverty, and inequality using a multidimensional poverty index, and a quasi‐experimental design that controls for potential confounding factors in non‐random treatment allocation. We specifically investigate the role of tourism in contributing to PA impacts. Nepali PAs reduced overall poverty and extreme poverty, and crucially, did not exacerbate inequality. Benefits occurred in lowland and highland regions, and were often greater when a larger proportion of the area was protected. Spread of benefits to nearby areas outside PAs was negligible. Furthermore, older PAs performed better than more recently established ones, suggesting the existence of time lags. Although tourism was a key driver of poverty alleviation, PAs also reduced extreme poverty in areas with fewer tourists.